Arterial stiffness and blood flow adaptations following eight weeks of resistance exercise training in young and older women - Rossow, Lindy M.; Fahs, Christopher A.; Thiebaud, Robert S.; Loenneke, Jeremy P.; Kim, Daeyeol; Mouser, James G.; Shore, Erin A.; Beck, Travis W.; Bemben, Debra A.; Bemben, Michael G. (Experimental gerontology, 2014)
Resistance training is recommended for all adults of both sexes. The arterial stiffness and limb blood flow responses to resistance training in young and older women have not been well-studied. The purpose of this study was to examine arterial stiffness and blood flow adaptations to high-intensity resistance exercise training in young and older women. Young (aged 18–25) and older (aged 50–64) women performed full-body high-intensity resistance exercise three times per week for eight weeks. The following measurements were performed twice prior to training and once following training: carotid to femoral and femoral to tibialis posterior pulse wave velocity (PWV), blood pressure, heart rate, resting forearm blood flow and forearm reactive hyperemia. Data was analyzed by ANOVAs with alpha set at 0.05. Correlations were also examined between changes in arterial stiffness and baseline arterial stiffness values. Older subjects had higher carotid–femoral PWV than younger subjects. No significant effects were found for femoral-tibialis posterior PWV or for resting forearm blood flow. Changes in carotid–femoral and femoral-tibialis posterior PWV correlated significantly with their respective baseline values. Older subjects increased peak forearm blood flow while young subjects showed no change. Total hyperemia increased significantly in both groups. In conclusion, in both young and older women, eight weeks of high-intensity resistance training appeared to improve microvascular forearm function while not changing carotid–femoral or femoral-tibialis posterior arterial stiffness. However, a large degree of individual variation was found and arterial stiffness adaptations appeared positively related to the initial stiffness values. •Resistance training did not stiffen the arteries of young or older women.•The training provided microvascular benefits, particularly in the older women.•Significant variation existed in these responses, however.